P1415Wide antral circumferential pulmonary vein isolation ablation using a novel balloon cryoablation catheter. (18th June 2020) - Martin, A P; Fowler, M; Lever, N
Abstract: Background: Pulmonary vein isolation using cryotherapy is an established treatment for the management of patients with paroxysmal atrial fibrillation. Ablation using the commercially available balloon cryocatheter has been shown to create wide antral pulmonary vein isolation. A novel balloon cryocatheter (BCC) has been designed to maintain uniform pressure and size during ablation, potentially improving contact with the antral anatomy. The extent of ablation created using the novel BCC has not previously been established. Purpose: To determine the anatomical extent of pulmonary vein isolation using electroanatomical mapping when performing catheter ablation for paroxysmal atrial fibrillation using the novel BCC. Methods: Nine consecutive patients underwent pre-procedure computed tomography angiography of the left atrium to quantify the chamber dimensions. An electroanatomical map was created using the cryoablation system mapping catheter and a high definition mapping system. A bipolar voltage map was obtained following ablation to determine the extent of pulmonary vein isolation ablation. A volumetric technique was used to quantify the extent of vein and posterior wall electrical isolation in addition to traditional techniques for proving entrance and exit block. Results: All patients had paroxysmal atrial fibrillation, mean age 56 years, 7 (78%) male. Electrical isolation was achieved for 100% of the pulmonary veins; mean total procedure time was 109 min (+/- 26 SD), and fluoroscopy time 14.9 min (+/- 2.4 SD). The median treatment applications per vein was one (range one - four), and median treatment duration 180 sec (range 180 -240). Left atrial volume 32 mL/m2 (+/- 7 SD), and mean left atrial posterior wall area 22 cm2 (+/- 4 SD). Data was available for quantitative assessment of the extent of ablation for eight patients. No lesions (0 of 32) were ostial in nature. The antral surface area of ablation was not statistically different between the left and right sided pulmonary veins (p 0.63), which were 5.9 (1.6 SD) and 5.4 (2.1 SD) cm2 respectively. In total 50% of the posterior left atrial wall was ablated.  Conclusion: Pulmonary vein isolation using a novel BCC provides a wide and antral lesion set. There is significant debulking of the posterior wall of the left atrium.